1997
DOI: 10.1111/j.1528-1157.1997.tb04523.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Animal Seizure Models and Mechanism of Action Studies of Potential Antiepileptic Drugs

Abstract: Summary: More than 50 million persons worldwide suffer from epilepsy, many of whom are refractory to treatment with standard antiepileptic drugs (AEDs Although epilepsy affects more than 50 million persons worldwide (l), the development of new pharmacologic interventions has lagged behind that of many other therapeutic categories. Until recently, physicians have had available a relatively limited armamentarium of antiepileptic drugs (AEDs) to treat patients with seizure disorders. This group of "standard" AEDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(134 citation statements)
references
References 55 publications
3
127
0
Order By: Relevance
“…It is possible to observe synergism between two drugs that modulate the function of one and the same neurotransmitter. A generally held principle is that two drugs sharing the same mechanism of action are not likely to interact synergistically (3)(4)(5). This is true when drugs exert their action through the same binding site, but in other cases, a synergistic interaction may occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to observe synergism between two drugs that modulate the function of one and the same neurotransmitter. A generally held principle is that two drugs sharing the same mechanism of action are not likely to interact synergistically (3)(4)(5). This is true when drugs exert their action through the same binding site, but in other cases, a synergistic interaction may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Important issues in the development of rational combination therapy are (a) identification of drug combinations that provide the largest degree of synergism with regard to the desired therapeutic effect, and (b) determination of the optimal dose ratio of such drugs. In theory, the largest degree of synergism is to be expected when two drugs with specific and differing mechanisms of action are combined (3)(4)(5). The combined response to two AEDs also depends on the concentrations of both drugs in the combination.…”
mentioning
confidence: 99%
“…The maximal electroshock (MES) test, the subcutaneous pentylenetetrazol (scPTZ) test, and the electrical kindling model are the most commonly used models to evaluate potential new AEDs [33][34][35][36][37]. In the MES test an electric current of fixed intensity and duration is applied via ear-clips or corneal electrodes resulting in tonic extension of the hindlimbs.…”
Section: Animal Screeningmentioning
confidence: 99%
“…The MES and scPTZ tests have markedly different pharmacological profiles [33]. The MES test identifies agents with activity against generalized tonic-clonic seizures while the scPTZ identifies compounds that are effective against absences and myoclonic seizures [38].…”
Section: Animal Screeningmentioning
confidence: 99%
“…Nevertheless, it has been shown that TGB is active in MES-test only at doses two-to three-fold higher than those producing motor impairment (more than 40 mg/kg; i.p.) (White, 1997). GBP at the dose of approximately 10 mg/kg; i.p., reduces MES-induced convulsions in rats, although the drug was reported to be completely inactive in mice (for a review, see Rogawski and Porter, 1990).…”
Section: Interaction Of Tiagabine With Gabapentinmentioning
confidence: 99%